Analysis of flavor formation and metabolite changes during production of Double-Layer Steamed Milk Custard made from buffalo milk - Hong Lan; Xier Luo; Dingyun Xu; Kuiqing Cui; Ling Li; Chuan Li; Hao Qi; Qingyou Liu (PLoS ONE, 2025)
Double-Layer Steamed Milk Custard (DLSMC) is a famous traditional Chinese dessert. This study aimed to analyze the flavor and the changes in metabolites during different stages of DLSMC preparation, including raw buffalo milk, thermo-processing, first and second-layer milk skin formation. Electronic nose and electronic tongue were employed to preliminarily assess the overall flavor characteristics between these stages. The results indicated that DLSMC demonstrated increased sweetness, saltiness, and umami compared to raw buffalo milk, along with heightened levels of nitrogen oxides, methane, alcohols, aldehydes, ketones, and sulfur-containing compounds. Thus, the thermo-processing and second-layer milk skin formation were pinpointed as critical for flavor alterations. Additionally, headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) detected a total of 46 volatile organic compounds (VOCs), with 8 compounds identified as key flavor components. Untargeted metabolomics revealed 98 differential metabolites, including amino acids, lipids, and nucleotides, that were significantly linked to changes in key flavor compounds. Indeed, the fluctuations in the levels of amino acids, lipids, and nucleotides play a crucial role in influencing flavor changes during the production of DLSMC made from buffalo milk.